Pengaruh Manajemen Talenta terhadap Kinerja Pegawai dengan Retensi Sebagai Variabel Intervening di Direktorat Jenderal Perbendaharaan - Pringadi Abdi Surya; Sriati Sriati; Abdul Nadjib (Direktorat Sistem Perbendaharaan, 2024)
Directorate General of Treasury implements talent management with the aim of finding/identifying, managing, developing, and retaining the best employees. This study aims to analyze the relationship between talent management, and employee retention and employee performance at the Directorate General of Treasury. The method is path analysis. The approach used in this research is quantitative with a survey method using a questionnaire. The results of the study show that talent management has a positive and significant effect on employee retention and employee performance at the Directorate General of Treasury. Nevertheless, several findings in this study indicate that there are some indicators which can still be improved.